Oxymatrine liposome attenuates hepatic fibrosis via targeting hepatic stellate cells - Chai, Ning-Li (Baishideng Publishing Group Co., Limited, 2012)
AIM: To investigate the potential mechanism of Arg-Gly-Asp (RGD) peptide-labeled liposome loading oxymatrine (OM) therapy in CCl(4)-induced hepatic fibrosis in rats. METHODS: We constructed a rat model of CCl(4)-induced hepatic fibrosis and treated the rats with different formulations of OM. To evaluate the antifibrotic effect of OM, we detected levels of alkaline phosphatase, hepatic histopathology (hematoxylin and eosin stain and Masson staining) and fibrosis-related gene expression of matrix metallopeptidase (MMP)-2, tissue inhibitor of metalloproteinase (TIMP)-1 as well as type I procollagen via quantitative real-time polymerase chain reaction. To detect cell viability and apoptosis of hepatic stellate cells (HSCs), we performed 3-(4,5)-dimethylthiahiazo(-z-y1)-3,5-diphenytetrazoliumromide assay and flow cytometry. To reinforce the combination of oxymatrine with HSCs, we constructed fluorescein-isothiocyanate-conjugated Arg-Gly-Asp peptide-labeled liposomes loading OM, and its targeting of HSCs was examined by fluorescent microscopy. RESULTS: OM attenuated CCl(4)-induced hepatic fibrosis, as defined by reducing serum alkaline phosphatase (344.47 ± 27.52 U/L vs 550.69 ± 43.78 U/L, P < 0.05), attenuating liver injury and improving collagen deposits (2.36% ± 0.09% vs 7.70% ± 0.60%, P < 0.05) and downregulating fibrosis-related gene expression, that is, MMP-2, TIMP-1 and type I procollagen (P < 0.05). OM inhibited cell viability and induced apoptosis of HSCs in vitro. RGD promoted OM targeting of HSCs and enhanced the therapeutic effect of OM in terms of serum alkaline phosphatase (272.51 ± 19.55 U/L vs 344.47 ± 27.52 U/L, P < 0.05), liver injury, collagen deposits (0.26% ± 0.09% vs 2.36% ± 0.09%, P < 0.05) and downregulating fibrosis-related gene expression, that is, MMP-2, TIMP-1 and type I procollagen (P < 0.05). Moreover, in vitro assay demonstrated that RGD enhanced the effect of OM on HSC viability and apoptosis. CONCLUSION: OM attenuated hepatic fibrosis by inhibiting viability and inducing apoptosis of HSCs. The RGD-labeled formulation enhanced the targeting efficiency for HSCs and the therapeutic effect.